The Underground Economy : Estimation, and Economic and Policy Implications; The Case of Pakistan - Shabsigh, Ghiath (IMF Working Papers; Working Paper, 1995)
This paper estimates the size of the underground economy in Pakistan and analyzes its impact on Government fiscal position and the allocation of economic resources in the national economy. The results suggest that there is a mutual dependency between the size of the underground economy and fiscal deficits, and show a leakage from the national income-expenditure cycle in the formal economy to the underground economy via private investments. Finally, the paper proposes long- and short-run policies to reduce the size of the underground economy.